Effect of culture conditions on the entomopathogenic activity of Serratia marcescens against Tocia solanivora (Lepidoptera: Gelechiidae) - BOSA-O., CARLOS FELIPE; COTES-P., ALBA MARINA (Revista Colombiana de Entomología, 2004)
A rnodel was established to evaluate the effect of successive inoculations and successive growths in culture media supplernented or not with potential virulence inductors (wheat bran and hornogenised Tecia so/anivora Povolny larvae) on the  enzymatic and biocontrol activity of Serratia marcescens. The  bacteria biornass obtained frorn these  media was evaluated for biocontrol activity against insect larvae, and enzyrnatic extracts were prepared to deterrnined the activity of the enzymes N-acetilglucosarninidase, quirnoelastase protease PR-1 and B-esterase. These activities were evaluated in each of five successive bacteria cultures. In general, both the type of substrate added to the media as well as successive growth affected the biocontrol and enzyrnatic activities, increasing in the third growth of the bacteria. The greatest biocontrol activities of S. marcescens, with or without activation in larvae, corresponding to 65 and 64% rnortality, respectively, were obtained when were the bacteria were grown in wheat bran rnediurn, followed by 58 and 59% rnortality, respectively, when grown in the larval rnediurn, activities that were significantly different than that obtained when S. marcescens grew in medium without supplernent (48,5%). In addition, a positive correlation was found between N-acetilglucosarninidase and quimoelastase protease activities and S. marcescens biocontrol activity, suggesting that the activity of these  enzyrnes could be related with the rnode of action of entomopathogenis bacteria of he genus Serratia.